Ibn Sina and the Harmony of Religion and Philosophy in Classical Islamic Thought - Yanti Lubis, Mira; Hasibuan, Sutan Botung; Akhirani, Nurhakimah; Siregar, Fithri Choirunnisa; Yossar, Yossar; AM, Rusydi; Saputra, Riki (STIT Ahlussunnah Bukittinggi, 2026)
This study aims to examine the philosophical thought of Ibn Sina within the framework of the classical Islamic intellectual tradition, with particular emphasis on the formation of his philosophical system, his synthesis of revelation and reason, and his metaphysical concepts of God and the soul. This research employs a qualitative method with a content analysis approach. Primary data are derived from Ibn Sina’s major philosophical works, while secondary data are obtained from relevant scholarly literature. The analysis is conducted through systematic coding, categorization, and interpretation of key themes related to metaphysics, theology, and philosophical synthesis, in order to identify patterns, conceptual structures, and underlying meanings in Ibn Sina’s thought. The findings indicate that Ibn Sina developed a coherent philosophical system that successfully integrates Greek rational philosophy with Islamic theological principles. His concept of Wajib al-Wujud (Necessary Being) positions God as the absolute and self-subsistent first cause, while his theory of the soul conceptualizes it as an immaterial, rational, and eternal substance. Furthermore, his framework demonstrates a systematic reconciliation between reason and revelation, reflecting a distinctive characteristic of classical Islamic intellectual tradition. The study implies that Ibn Sina’s philosophical synthesis remains relevant for contemporary intellectual discourse, particularly in addressing the relationship between religion and rationality. It also underscores the significant contribution of classical Islamic philosophy to global philosophical development and provides a conceptual foundation for further research using interdisciplinary and comparative approaches.